2021
DOI: 10.1007/s40121-021-00486-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Incidence of COVID-19-Associated Pulmonary Aspergillosis (CAPA) in a Greek Tertiary Care Academic Reference Hospital

Abstract: Introduction: Invasive pulmonary aspergillosis is an emerging complication among intensive care unit (ICU) patients with COVID-19 (CAPA). In the present study, all CAPA cases during the first year of the pandemic were reviewed in critically ill patients at a 650-bed tertiary Greek COVID-19 reference hospital. Methods: Data regarding patients admitted to the ICU of Attikon Hospital in Athens, Greece, between 22 March 2020 and 28 February 2021 with a positive PCR for SARS-CoV-2 infection were reviewed. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…Several factors caused a wide variability in the incidence of CAPA in retrospective (and to a lesser extent prospective) observational trials. The first factor is a regional difference in CAPA incidence, e.g., reported incidences have been as low as 3.3% in Greece and as high as 38.7% in Germany (Figure 2) [2,18,22,31]. Whether this is solely caused by regional differences in test strategies (further discussed below), or also by other regional factors, such as differences in circulating SARS-CoV2 strains, deserves further investigation.…”
Section: Incidencementioning
confidence: 99%
“…Several factors caused a wide variability in the incidence of CAPA in retrospective (and to a lesser extent prospective) observational trials. The first factor is a regional difference in CAPA incidence, e.g., reported incidences have been as low as 3.3% in Greece and as high as 38.7% in Germany (Figure 2) [2,18,22,31]. Whether this is solely caused by regional differences in test strategies (further discussed below), or also by other regional factors, such as differences in circulating SARS-CoV2 strains, deserves further investigation.…”
Section: Incidencementioning
confidence: 99%
“…[ 23 ]; [ 24 ]; [ 25 ]; [ 26 ]; [ 27 ]; [ 28 ]; [ 29 ]; [ 30 ]; [ 31 ]; [ 32 ]; [ 33 ]; [ 34 ]; [ 35 ]; [ 36 ]; [ 37 ]; [ 38 ]; [ 39 ]; [ 40 ]; [ 41 ]; [ 42 ]; [ 43 ]; [ 44 ]; [ 45 ]; [ 46 ]; [ 47 ]; [ 48 ]; [ 49 ]; [ 50 ]; [ 51 ]; [ 52 ]; [ 53 ]; [ 54 ]; [ 55 ]; [ 56 ]; [ 57 ]; [ 58 ]; [ 59 ]; [ 60 ]; [ 61 ]; [ 62 ]; [ 63 ]; [ 64 ]; [ 65 ]; [ 66 ]; [ 67 ]; [ 68 ]; [ 69 ].…”
Section: Uncited Referencesunclassified
“…The incidence of CAPA in our study was around 5%. Previous studies have shown incidences varying from 3 to 34% [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Practices in obtaining specimens such as tracheal or endotracheal aspirates, bronchoscopy specimens, fungal biomarkers as well local geographic variations in the incidence of Aspergillus likely contributed to these variations.…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)associated pandemic, multiple reports of IPA have emerged in critically ill patients with severe pneumonia [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The incidence of COVID-19-associated pulmonary aspergillosis (CAPA) in these studies has been variable, ranging from 3 to 34% largely due to differences in diagnostic criteria as well as regional differences in obtaining culture specimens and bronchoscopies [14,26].…”
Section: Introductionmentioning
confidence: 99%